Ear Throat Nose Otorhinolaryngological Diseases And Phytopreparations Used For Them Use Of The Sarsabil And Licorice Extracts, Eucalyptus, Afsonak, Plants In Pharmaceutical And Folk Medicine (The Peerian Journal, 2024)
It is an unproven fact that patients cannot be successfully treated without effective drugs. Determining the important importance of medicinal plants in the territory of our republic in protecting, restoring and strengthening the health of the population has risen to the level of state policy today. The creation of highly effective medicinal preparations or the acquisition of biologically active substances known in science from new sources and based on them the creation of medicinal preparations with a wide range of effective therapeutic pharmacological action is an urgent issue facing pharmaceutical and medical practice. Currently, technologies for obtaining slow and long-acting drugs are being developed using the combination of large molecular compounds with medicinal substances and other scientifically based methods. This article provides practical and theoretical comparisons of new information about our local medicinal plants, which have a wide range of effects on ear, nose, and throat diseases.